Social network size affects neural circuits in macaques - Sallet, J; Mars, R B; Noonan, M P; Andersson, J L; O'Reilly, J X; Jbabdi, S; Croxson, P L; Jenkinson, M; Miller, K L; Rushworth, M F S (Science (American Association for the Advancement of Science), 2011)
It has been suggested that variation in brain structure correlates with the sizes of individuals' social networks. Whether variation in social network size causes variation in brain structure, however, is unknown. To address this question, we neuroimaged 23 monkeys that had been living in social groups set to different sizes. Subject comparison revealed that living in larger groups caused increases in gray matter in mid-superior temporal sulcus and rostral prefrontal cortex and increased coupling of activity in frontal and temporal cortex. Social network size, therefore, contributes to changes both in brain structure and function. The changes have potential implications for an animal's success in a social context; gray matter differences in similar areas were also correlated with each animal's dominance within its social network.